Role of carbon on the thermal and electrical properties of graphene- enriched silicon oxycarbides. Issue 18 (15th December 2020) - Gangadhar, Jella; Maheshwari, Ankur; Bordia, Rajendra K.; Shyam Kumar, C.N.; Kubel, Christian; Sujith, Ravindran
Abstract: In this study, we demonstrate the effect of incorporation of graphene nanoplatelets (GNP) on the electrical and thermal properties of silicon oxycarbide polymer-derived ceramics (PDC) pyrolyzed at 1000 °C. Silicon oxycarbide PDCs were synthesized by the pyrolysis of polymethylhydrosiloxane and divinylbenzene to produce a ceramic with high free carbon content. Besides, GNP of 3 and 6 wt% was added to the ceramic, and the structure of these ceramic composites was investigated using X-ray photoelectron spectroscopy, Raman spectroscopy, X-ray diffraction (XRD), and high-resolution transmission electron microscopy (HR-TEM). Fourier transform infrared spectroscopy, and thermogravimetric studies indicated that the addition of GNP has not affected the curing and the ceramization process. XRD studies showed that no crystalline phases were present except that of carbon in the GNP added systems. The electrical conductivity increased by four orders of magnitude (from 9.89 × 10 -5 to 1.2 × 10 -1 Scm -1 ), whereas, thermal conductivity values showed an increase of 44% by the addition of 6 wt% GNP. HR-TEM study revealed that the free carbon present in the unmodified Si-O-C is predominantly disordered, and its contribution to the improvement in properties is less in comparison with ordered GNP. GNP has formed interconnected networks, and its better-ordered structure resulted in the sharp increase in properties, especially electrical conductivity.